Migrant memories, exclusion and belonging, the case of Goiânia - de Bessa, Suzete (2023)
This article seeks to highlight the dynamics of memories without a place and their consequences in conflicts and potentialities in Goiânia, identifying how they result in exclusion and belonging, and imply the valorization of the experience and voice of migrants in the city. To this end, it intends to present conclusions from research in architecture and urbanism initiated in 2019 at the Federal University of Bahia that were presented to postgraduate researchers, being built concomitantly with the development of extension projects with Venezuelan migrants and refugees in Goiânia and its metropolitan region, in the State of Goiás. The work at the time sought, through a semi-structured investigation, to establish a dialogue about the complexity of the elaboration of memories in the context of migrations, considering the political moment, trying to apply such dialogues to the specific local scenario and their diversified migratory profiles. Faced with an incipient investigation, some mobilized theories turned out to be imprecise and some authors absolutely necessary for the dialogue were exempted from the debate. Today, three years after the beginning of the research, which occurred with a single family nucleus, and after a hiatus dedicated to the maturation and deepening of the methodological practice, it was extended to other nuclei or migrant and refugee families in Goiânia. In this way, it seeks to review what was proposed in the first work, in order to reconsider it and its conclusions based on a careful methodological description, positioning highly relevant authors and researchers in its construction.